2021
DOI: 10.31117/neuroscirn.v4i3suppl.97
|View full text |Cite
|
Sign up to set email alerts
|

Association between hand-grip strength and risk of stroke among Mongolian adults: Results from a population-based study

Abstract: Mongolia ranks third in the world in stroke-related deaths. Loss of skeletal muscle mass and function, known as sarcopenia, is associated with a higher risk of various metabolic disorders such as stroke. Thus, screening of sarcopenia is important. Hand-grip strength (HGS) can be used to predict sarcopenia in the short term. In this cross-sectional study, we used data (n=1180, mean age of 39.2 ± 15.2 and 33.2% males) from the Mon-Timeline cohort study, a multidisciplinary, prospective, population-based cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
(44 reference statements)
1
6
0
Order By: Relevance
“…As a result, the current study has identified creatinine differences by HGS with an age effect. The participants were divided into two groups, those with high HGS (>25 percentile) and low HGS (<25 per percentile); this threshold criterion was found in a previous study in the same population [ 21 ]. There were certain associations for the urinary creatine concentration in relation to HGS groups and age groups in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the current study has identified creatinine differences by HGS with an age effect. The participants were divided into two groups, those with high HGS (>25 percentile) and low HGS (<25 per percentile); this threshold criterion was found in a previous study in the same population [ 21 ]. There were certain associations for the urinary creatine concentration in relation to HGS groups and age groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were instructed to continually tighten the handle with full force for at least 3 s and not to move the dynamometer or hold their breath while taking the measurement. The measures were the same for men and women and age groups, but we used different thresholds that had been established before in the same population [ 21 ]. The maximal measurement for one of the two hands was taken and called the dominant HGS [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instrument can measure hand-grip values from 5 to 100 kg; the minimum unit of measurement is 0.1 kg. The tool is a good health outcomes predictor [ 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…To measure HGS, a digital grip strength dynamometer (factory standardized and certified) was used that was made in Japan (Takei Hand Grip Dynamometer 5401-C) [ 16 ]. The instrument is capable of measuring from 5 to 100 kg and the measurements are recorded with 0.1 kg accuracy.…”
Section: Methodsmentioning
confidence: 99%